2018
DOI: 10.1016/j.ijom.2018.01.005
|View full text |Cite
|
Sign up to set email alerts
|

An innovative virtual reality training tool for orthognathic surgery

Abstract: Virtual reality (VR) surgery using Oculus Rift and Leap Motion devices is a multi-sensory, holistic surgical training experience. A multimedia combination including 360° videos, three-dimensional interaction, and stereoscopic videos in VR has been developed to enable trainees to experience a realistic surgery environment. The innovation allows trainees to interact with the individual components of the maxillofacial anatomy and apply surgical instruments while watching close-up stereoscopic three-dimensional vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
68
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(70 citation statements)
references
References 16 publications
0
68
0
2
Order By: Relevance
“…Though widely considered by the public to be an entertainment technology, VR has demonstrated utility in a variety of applications, ranging from preparing surgeons and patients for operations and aiding in mental health, to education in bioscience, chemistry, physics and engineering (Borrel & Fourches, 2017;Botella, Serrano, Banos, & Garcia-Palacios, 2015;Cha et al, 2016;Chirico et al, 2016;Cho et al, 2002;Goddard et al, 2018;Hoffman et al, 2008;O'Connor et al, 2018;Parkhomenko et al, 2018;Pulijala, Ma, Pears, Peebles, & Ayoub, 2018a, 2018bTeranishi & Yamagishi, 2018). Multiple studies have demonstrated the effectiveness of VR in healthcare scenarios, including: (i) improved informed consent by allowing patients to visualise recommended procedures (Parkhomenko et al, 2018), (ii) pain management (Chirico et al, 2016;Hoffman et al, 2008), (iii) Post Traumatic Stress Disorder treatment (Botella et al, 2015), and (iv) preparing surgeons for surgery (Cha et al, 2016;Parkhomenko et al, 2018;Pulijala et al, 2018aPulijala et al, , 2018b. Additionally, Cho and colleagues (Cho et al, 2002) observed that juvenile delinquents saw greater improvements in their attention spans when they underwent cognitive training courses in HMD VR compared to using a standard flat-screen computer.…”
Section: Vr -More Than Just a Gamementioning
confidence: 99%
See 1 more Smart Citation
“…Though widely considered by the public to be an entertainment technology, VR has demonstrated utility in a variety of applications, ranging from preparing surgeons and patients for operations and aiding in mental health, to education in bioscience, chemistry, physics and engineering (Borrel & Fourches, 2017;Botella, Serrano, Banos, & Garcia-Palacios, 2015;Cha et al, 2016;Chirico et al, 2016;Cho et al, 2002;Goddard et al, 2018;Hoffman et al, 2008;O'Connor et al, 2018;Parkhomenko et al, 2018;Pulijala, Ma, Pears, Peebles, & Ayoub, 2018a, 2018bTeranishi & Yamagishi, 2018). Multiple studies have demonstrated the effectiveness of VR in healthcare scenarios, including: (i) improved informed consent by allowing patients to visualise recommended procedures (Parkhomenko et al, 2018), (ii) pain management (Chirico et al, 2016;Hoffman et al, 2008), (iii) Post Traumatic Stress Disorder treatment (Botella et al, 2015), and (iv) preparing surgeons for surgery (Cha et al, 2016;Parkhomenko et al, 2018;Pulijala et al, 2018aPulijala et al, , 2018b. Additionally, Cho and colleagues (Cho et al, 2002) observed that juvenile delinquents saw greater improvements in their attention spans when they underwent cognitive training courses in HMD VR compared to using a standard flat-screen computer.…”
Section: Vr -More Than Just a Gamementioning
confidence: 99%
“…Several of these programmes focus on the visualisation of atoms and molecules whilst using a HMD VR system (Borrel & Fourches, 2017;Goddard et al, 2018;O'Connor et al, 2018), and others facilitate the study of electron and light microscopy (Goddard et al, 2018), though the benefits of these tools after course implementation have not been described. Many other educational VR programmes have been developed and their benefits on learning outcomes studied in the fields of biomedical science education (Brewer et al, 2012;Codd & Choudhury, 2011;Garg, Norman, & Sperotable, 2001;Garg, Norman, Eva, Spero, & Sharan, 2002;Garg, Norman, Spero, & Maheshwari, 1999;Maresky et al, 2019;Marsh et al, 2008;Stepan et al, 2017), medical preparation and training (Cha et al, 2016;Harrington et al, 2018;Parkhomenko et al, 2018;Pulijala et al, 2018aPulijala et al, , 2018b, as well as in computer engineering (Teranishi & Yamagishi, 2018). Furthermore, Mahaffey et al have previously designed an undergraduate physiology course with a focus on the implementation of VR physiology laboratories alongside a variety of e-learning resources (such as electronic textbooks, online home-work and animations), face-to-face classes, and student led case studies (Mahaffey, 2018).…”
Section: A Breadth Of Applicationsmentioning
confidence: 99%
“…In 4 studies, the aim was to compare the performance of MK with that of a mouse [5,79,80,96]; in 1 study, it was to compare the performance of the LMC with that of a mouse [81]; and in 4 studies, it was to compare different COTS devices [52,58,77,113]. In 10 studies, the aim was to evaluate face validity [97,120], content validity [97], construct validity [66,110,111,120,121,126,127,132], or concurrent validity of the devices [66,71,121,126]. A total of 7 studies involved experiments [19,26,113,115,122,123,131] and there was 1 patent application for an LMC-based application [124] and 1 interrater reliability study [72].…”
Section: Resultsmentioning
confidence: 99%
“…Compared to the VR environment using HMD, the problem of resolution caused by small tooth size is one of the most important problems to be solved. Pulijala et al[18] reported on VR simulation for orthgnathic surgery training and reported that it is useful for educator's experience improvement and training of various surgical tools. However, compared to orthognathic surgery, tooth preparation is very small and elaborate, making it difficult to practice and evaluate the current resolution.…”
mentioning
confidence: 99%